A case report of collecting duct carcinoma of the kidney coexistent with giant adrenal myelolipoma - Li, Bingkun; Ding, Qiang (Canadian Urological Association Journal, 2013)
Collecting duct carcinoma (CDC) of the kidney coexistent with giant adrenal myelolipoma is rare. We report a case of 70-year oldfemale who presented with a history of gross hematuria and back pain. On investigation, she had a mass in the left kidney and left adrenal gland, respectively. The patient underwent left radical nephrectomy with left adrenalectomy. Pathological findings revealed a renal CDC with partial aquamous metaplasia, in addition to an adrenal myelolipoma. Interleukin-2 was administered for 3 months after operation. Neither signs of recurrence nor metastasis has developed after a 4-year follow-up.